Childhood Neuroblastoma: Incidence and Survival in Argentina. Report from the National Pediatric Cancer Registry, ROHA Network 2000–2012. Issue 8 (2nd May 2016) - Moreno, Florencia; Lopez Marti, Jessica; Palladino, Marcela; Lobos, Pablo; Gualtieri, Ariel; Cacciavillano, Walter
Abstract : Background: There are reports indicating a low incidence of neuroblastoma (NB) in some developing countries but no conclusive data are available from population‐based studies at a national level. Purpose: To describe the incidence and survival of 971 patients with NB in Argentina with data from the National Pediatric Cancer Registry (ROHA), and the impact of age, gender, stage, regional, and socioeconomic indicators on outcome. Methods: All cases of NB reported to ROHA (2000–2012) were the subject of the analysis. Annual‐standardized incidence rate (ASR) was calculated using the National Vital Statistics and survival was estimated. The extended human development index (EHDI) was used as the socioeconomic indicator. Results: ASR was 8.3/1, 000, 000 children (0–14 years) and remained stable along this period. Regional variation in ASR ranged from 3.4 in the Northwest to 9.8 in the Central region, being most marked in the first year of life. Five‐year survival rate (SR) was 47%, with no sex difference. For patients older than 18 months, it was 36%, for stage IV 23%, for those born in the Northeast region 38%, and for those with an amplified MYCN 15%. Residents in provinces with a higher EHDI had a better 5‐year survival (57% vs. 41% for lower EHDI) and higher ASR (12.3 vs. 5.6 for lower EHDI). Stage and MYCN status showed an independent inferior prognosis. Conclusions: ASR of NB in Argentina is lower than in developed countries, with considerable regional variation. SRs are also lower than in developed countries.